ABOUT ONE STOCHASTIC MODEL OF CONDENSATION OF WATER VAPOR IN ATMOSPHERE - Musarbi Kilyanievich Makuashev (Наука. Инновации. Технологии, 2022)
In the present work the theory of condensation from the point of view of the theory of stochastic processes is developed.